Perceptions of Social Studies Teachers on Teaching Rationale in New Juaben Senior High Schools, Ghana: A Qualitative Study - Patrick , Yeyie (Social Education Research, 2024)
This study explored how Social Studies teachers perceived the rationale for teaching and learning Social Studies in the New Juaben Senior High Schools in the Eastern Region of Ghana. Negative attitudes and behaviour among the youth in schools and after are becoming a great concern to Ghanaian society. The rationale for teaching and learning the subject is to produce good citizens. The above indicates that Social Studies as a subject is capable of developing positive attitudes and values in learners to bring about a reduction if not eradication, of negative attitudes among the youth in school and beyond school. For a subject to achieve its core mandate or rationale depends mainly on the teacher. It is based on the above that this research seeks to investigate how the teachers perceived the rationale for teaching and learning the subject at the Senior High Schools in the country. The research made use of qualitative design, using semi-structured interviews to explain and improve qualitative data knowledge. The simple random sampling precisely the lottery method was used to choose a sample size of 24 Social Studies teachers for the study. The study found that most of the teachers perceived the rationale for teaching the subject at the Senior High School as good and capable of producing good and responsible citizens. It is recommended that Social Studies teachers at the Senior High Schools should teach the subject along the rationale of the subject to produce responsible citizens.